Cellulose ultrafine fibers embedded with titania particles as a high performance and eco-friendly separator for lithium-ion batteries - Dul Boriboon (2019)
© 2018 Mixtures of cellulose acetate (M.W. ∼3 × 104 g/mol) dissolved in 75% v/v acetic acid in water (17% w/w) and ground anatase titania particles with diameters of 197 ± 75 nm (0%, 5% and 10% w/w) were electrospun at 17 kV with a fiber collection distance and a feed rate of 10 cm and 0.6 mL/h. Then, the fiber was treated with 0.5 M potassium hydroxide in ethanol. Rough regenerated cellulose (RC)–titania separators with diameters of ∼310 nm and uniformly dispersed titania particles showed ∼78% porosities. They decomposed at 300 °C, higher than the decomposition temperature of polyethylene separators (220 °C). Added titania particles increased the electrolyte wettability and lithium transference number (from 0.22 to 0.62). RC – 10% titania separator retained the capacity with 79 mA h/g after 30 cycles and had excellent discharge capacity. These fascinating properties make RC–titania separator promising for lithium ion battery.